Sick of Working from Home? - Dominique Goux; Eric Maurin (Institute of Labor Economics (IZA), 2024)
Driven by new information technologies, working from home has experienced unprecedented growth since the COVID pandemic. We contribute to the debate on the consequences of this development by drawing on a French reform conducted in 2017, with the aim of facilitating telework agreements between employers and employees. We show that the reform was followed by a boom in working from home, particularly in mid-level occupations. On the other hand, employees in lower-level occupations were virtually unaffected. By comparing occupational groups before and after the reform, in firms that have signed telework agreements and in firms that have not, we find that the development of working from home coincides with a significant deterioration in the health status of mid-level employees, particularly men. Wages and number hours worked, on the other hand, remain largely unaffected.
Keywords: J81; J53; I19; 330; occupational level; teleworking; health status; working from home